Analyzing Gender-Related Factors Toward the Purchase Intention of Male Skincare Products in Indonesia - Elfi Elfi (Jurnal Nomosleca, 2023)
Male skincare products are growing in Indonesia along with the metrosexual phenomenon. However, Indonesian culture is not completely ready for metrosexual behavior and more Indonesian men do not identify themselves as metrosexuals, and yet still use skincare, at least facial wash. This study seeks to investigate gender-related constructs influencing the purchase intention of male skincare products. The exogenous variables in this research are the need for product gender congruence, purchase secrecy, and product attributes (focusing on packaging design and the â€œFor Menâ€ label only). 112 respondents who meet the criteria of 17 years and above, use skincare â€“ at least facial wash, and care for their appearance but do not associate themselves with metrosexuals, are included in the analysis. PLS-SEM is employed in this study and the results support all the hypotheses tested.Â Â